Research on the intermediate process of a free-piston linear generator from cold start-up to stable operation: Numerical model and experimental results. (15th August 2016) - Feng, Huihua; Guo, Chendong; Jia, Boru; Zuo, Zhengxing; Guo, Yuyao; Roskilly, Tony
Highlights: The intermediate process of free-piston linear generator is investigated for the first time. "Gradually switching strategy" is the best strategy in the intermediate process. Switching at the top dead center position timing has the least influences on free-piston linear generator. After the intermediate process, the operation parameters value is smaller than those before the intermediate process. Abstract: The free-piston linear generator (FPLG) has more merits than the traditional reciprocating engines (TRE), and has been under extensive investigation. Researchers mainly investigated on the starting process and the stable generating process of FPLG, while there has not been any report on the intermediate process from the engine cold start-up to stable operation process. Therefore, this paper investigated the intermediate process of the FPLG in terms of switching strategy and switching position based on simulation results and test results. Results showed that when the motor force of the linear electric machine (LEM) declined gradually from 100% to 0% with an interval of 50%, and then to a resistance force in the opposite direction of piston velocity (generator mode), the operation parameters of the FPLG showed minimal changes. Meanwhile, the engine operated more smoothly when the LEM switched its working mode from a motor to a generator at the piston dead center, compared with that at the middle stroke or a random switching time. More importantly, after the intermediate process, the operation parameters of FPLG were smaller than that before the intermediate process. As a result, a gradual motor/generator switching strategy was recommended and the LEM was suggested to switch its working mode when the piston arrived its dead center in order to achieve smooth engine operation.